DO3SE modelling of soil moisture to determine ozone flux to forest trees - Büker, P.; Morrissey, T.; Briolat, A.; Falk, R.; Simpson, D.; Tuovinen, J.-P.; Alonso, R.; Barth, S.; Baumgarten, M.; Grulke, N.; Karlsson, P. E.; King, J.; et al. (Atmospheric Chemistry and Physics, 2012)
The DO3SE (Deposition of O3 for Stomatal Exchange) model is an established tool for estimating ozone (O3) deposition, stomatal ﬂux and impacts to a variety of vegetation types across Europe. It has been embedded within the EMEP (European Monitoring and Evaluation Programme) photochemical model to provide a policy tool capable of relating the ﬂux-based risk of vegetation damage to O3 precursor emission scenarios for use in policy formulation. A key limitation of regional ﬂux-based risk assessments has been the assumption that soil water deﬁcits are not limiting O3 ﬂux due to the unavailability of evaluated methods for modelling soil water deﬁcits and their inﬂuence on stomatal conductance (gsto), and subsequent O3 ﬂux. This paper describes the development and evaluation of a method to estimate soil moisture status and its inﬂuence on gsto for a variety of forest tree species. This DO3SE soil moisture module uses the Penman-Monteith energy balance method to drive water cycling through the soil-plantatmosphere system and empirical data describing gsto relationships with pre-dawn leaf water status to estimate the biological control of transpiration. We trial four different methods to estimate this biological control of the transpiration stream, which vary from simple methods that relate soil water content or potential directly to gsto, to more complex methods that incorporate hydraulic resistance and plant capacitance that control water ﬂow through the plant system. These methods are evaluated against ﬁeld data describing a variety of soil water variables, gsto and transpiration data for Norway spruce (Picea abies), Scots pine (Pinus sylvestris), birch (Betula pendula), aspen (Populus tremuloides), beech (Fagus sylvatica) and holm oak (Quercus ilex) collected from ten sites across Europe and North America. Modelled estimates of these variables show consistency with observed data when applying the simple empirical methods, with the timing and magnitude of soil drying events being captured well across all sites and reductions in transpiration with the onset of drought being predicted with reasonable accuracy. The more complex methods, which incorporate hydraulic resistance and plant capacitance, perform less well, with predicted drying cycles consistently underestimating the rate and magnitude of water loss from the soil. A sensitivity analysis showed that model performance was strongly dependent upon the local parameterisation of key model drivers such as the maximum gsto, soil texture, root depth and leaf area index. The results suggest that the simple modelling methods that relate gsto directly to soil water content and potential provide adequate estimates of soil moisture and inﬂuence on gsto such that they are suitable to be used to assess the potential risk posed by O3 to forest trees across Europe.
Keywords: DO3SE; Drought (voyant); Modeling; soil water; Stomatal conductance; Stomatal ozone ﬂux

Contribution of physiological and morphological adjustments to drought resistance in two Mediterranean tree species - Serrano, L.; Penuelas, J. (Biologia Plantarum, 2005)
Plant water potential (ψ), its components, and gas exchange data of two Mediterranean co-occurring woody species (Quercus ilex L. and Phillyrea latifolia L.) were measured in response to seasonal changes in water availability over two consecutive years. The relative contribution of physiological and morphological adjustments to drought resistance was assessed through Principal Component Analyses. There were large adjustments in stomatal conductance (~36 % of accounted variance). Net photosynthetic rate and water use efficiency were closely tuned to water availability and accounted for ~17 % of variance. The slope of the water potential vs. relative water content (dψ/dRWC0) below zero pressure potential increased as a result of seasonal and ontogenic increases in apoplastic water fraction and accounted for ~20 % variance. This tolerance mechanism was accompanied by an increased range of positive pressure potential, suggesting a functional role of sclerophylly in these Mediterranean evergreens. Similarly, changes in the slope of dψ/dRWC in the range of positive pressure potential (~13 % of accounted variance) were associated to variations in cell wall elasticity and resulted in lower RWC at zero pressure potential. When considering the species studied separately, the results indicated the primary role of stomatal regulation in the drought resistance of Q. ilex, while increased apoplastic water fraction had a major contribution in the drought resistance of P. latifolia.
Keywords: Drought stress; net photosynthetic rate; phillyrea latifolia; plant and tissue-water relations; Quercus ilex; Stomatal conductance; water potential

Comparative field study of spring and summer leaf gas exchange and photobiology of the mediterranean trees Quercus ilex and Phillyrea latifolia - Penuelas, J.; Filella, I.; Llusia, J.; Siscart, D.; Piñol, J. (Journal of Experimental Botany, 1998)
Summer-induced changes in gas exchange, fluorescence and reflectance were measured on leaves of two co-occurring Mediterranean small trees, Quercus ilex and Phillyrea latifolia, in May, June and July 1996 in Central Catalonia (NE Spain). The humid 1996 summer only produced mild water stress conditions. However, photosynthesis (A) and stomatal conductance (gs) decreased in June and July in both species. In June P. latifolia had higher net photosynthetic rates and lower stomatal conductances than Q. ilex, thus exhibiting higher instantaneous plant water use efficiencies. In agreement with these results, the photo-chemical reflectance index (PRI, calculated as (R570-R531)/(R531+R570)) of P. latifolia was lower, suggesting a possible lower xanthophyll de-epoxidation state. However, P. latifolia had lower ΔF/F′ and therefore a lower electron transport rate (ETR). The behaviour of PRI confirmed previous studies indicating a strong relationship between PRI, ΔF/F′ , and photosynthetic radiation-use efficiency (PRUE). PRI offers a simple, portable means of assessing PRUE with the potential for remote sensing applications. Finally, the possible ecological consequences of these results on the behaviour of the two species studied under the predicted warmer and drier conditions of global change are discussed.
10.1093/jxb/49.319.22910.1093/jxb/49.319.229
Keywords: fluorescence; intrinsic water use efficiency; net photosynthetic rates; phillyrea latifolia; photochemical efficiency; photochemical reflectance index; photosynthetic radiation-use-efficiency; Quercus ilex; reflectance; Stomatal conductance; summer; water index

Leaf gas exchange and ﬂuorescence of Phillyrea latifolia, Pistacia lentiscus and Quercus ilex saplings in severe drought and high temperature conditions - Filella, I.; Llusia, J.; Piñol, J.; Penuelas, J. (Environmental and Experimental Botany, 1998)
Saplings of Phillyrea latifolia, Pistacia lentiscus and Quercus ilex were witheld watering for 7 days, followed by reirrigation. Incident photosynthetic photon ﬂux density (PPFD), leaf temperature, net photosynthetic rates, stomatal conductance, and photochemical efﬁciency of the photosystem II (DF:F’m) were measured three times during the day. The watered plants had higher photosynthetic rates, stomatal conductances, DF:F’m and ETR than non-watered plants. However, watered plants were mildly water stressed as shown by low ratio of variable to maximal ﬂuorescence (Fv:Fm) and high non-photochemical ﬂuorescence quenching (qN). Their DF:F%m was low in the morning and increased in the evening, following the variations in PPFD. Watered plants of Q. ilex had lower photosynthetic activity, stomatal conductance and photosynthetic radiation use efﬁciency than Ph. latifolia and P. lentiscus, and, conversely, reached the highest DF:F%m and ETR. This seems to indicate a different relationship between photosynthetic activity and electron transport rate in Q. ilex compared to the other two species. Ph. latifolia and P. lentiscus appeared to be better adapted to severe drought than Q. ilex.
Keywords: Drought; hF/F’m; phillyrea latifolia; photosynthetic rate; Pistacia lentiscus; Quercus ilex; Stomatal conductance